2011
DOI: 10.1007/s11144-011-0336-x
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Cr2O3·3Al2O3 and Au–Cu/Cr2O3·3Al2O3 catalysts for methanol synthesis and water gas shift reactions

Abstract: A comparative study of the physicochemical properties of Cu/ Cr 2 O 3 Á3Al 2 O 3 and Au-Cu/Cr 2 O 3 Á3Al 2 O 3 supported catalysts and their catalytic activity in methanol synthesis and water gas shift reactions were the main subject of this study. The promotion effect of gold addition to Cu/support catalysts in the methanol synthesis reaction was proved. The formation of an Au-Cu alloy was confirmed by XRD technique. Methanol selectivity increased after gold introduction onto the catalyst surface, which can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…[19] investigated the phase composition of copper-chromium(III) catalysts and they also confirmed the formation of copper chromite spinel-like structure (CuCr 2 O 4 ) and small quantities of a-Cr 2 O 3 [20]. In our previous works [13,14,21], we obtained similar results. We studied the phase composition of copper supported catalysts calcined in air at 400°C and reported that copper catalysts were a mixture of CuO, a-Cr 2 O 3 , CuCr 2 O 4 and amorphous Al 2 O 3 phases.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…[19] investigated the phase composition of copper-chromium(III) catalysts and they also confirmed the formation of copper chromite spinel-like structure (CuCr 2 O 4 ) and small quantities of a-Cr 2 O 3 [20]. In our previous works [13,14,21], we obtained similar results. We studied the phase composition of copper supported catalysts calcined in air at 400°C and reported that copper catalysts were a mixture of CuO, a-Cr 2 O 3 , CuCr 2 O 4 and amorphous Al 2 O 3 phases.…”
Section: Resultssupporting
confidence: 72%
“…The formation of spinel structure compounds was caused by solid-solid interactions of CuO with c-Al 2 O 3 , and CuO with a-Cr 2 O 3 at temperatures above 700°C during the calcination process. In our previous work, the phase composition studies of calcined monometallic copper catalysts supported on CrAl 3 O 6 or spinellike structure ZnAl 2 O 4 confirmed the formation of copper chromite [13,14] and copper aluminate [8,22] spinel-like structure depending on the catalyst composition.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…6). This single reduction stage was situated in the temperature range 300-580°C, which is connected with the reduction of Cr(VI) oxidized phase formed from the previously re-oxidized phase of Cr 2 O 3 [22][23][24][25][26]. The obtained results also clearly indicate that the highest hydrogen consumption peak was observed for Al 2 O 3 -Cr 2 O 3 (2:1) system.…”
Section: Resultsmentioning
confidence: 58%
“…Other than that, the addition of aurum has also been found to affect the performance of Cu-based catalyst. In the work by Mierczynski [34], 20% Cu/Cr 2 O 3 /3Al 2 O 3 gave the highest methanol yield and 5% Au-20% Cu/Cr 2 O 3 /3Al 2 O 3 showed the highest selectivity for methanol synthesis. High selectivity could be due to the formation of Au-Cu alloy and that Au particle in the catalyst that served as nucleation center for Cu crystallization.…”
Section: Effect Of Promoter On the Catalyst Systemmentioning
confidence: 98%